2005
DOI: 10.1002/nau.20174
|View full text |Cite
|
Sign up to set email alerts
|

Sacral versus pudendal nerve stimulation for voiding dysfunction: A prospective, single‐blinded, randomized, crossover trial

Abstract: This is the first blinded study of sacral versus pudendal stimulation for voiding dysfunction. Successful implantation of a pudendal lead was achieved in all subjects. The majority of subjects chose PNS to be superior to SNS. More patients and longer term data is needed to confirm these promising results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
129
0
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 181 publications
(144 citation statements)
references
References 9 publications
1
129
0
7
Order By: Relevance
“…A potential benefit is increased afferent stimulation to the micturition centre through all three sacral nerve roots. We recently reported our acute comparative results of SNS vs PNS for various voiding dysfunctions, and the present study is a subset analysis of those with IC in that trial [9]. There have been no reports of chronic PNS in patients with IC, but a recent small study on overactive bladder was reported [10].…”
Section: Discussionmentioning
confidence: 88%
“…A potential benefit is increased afferent stimulation to the micturition centre through all three sacral nerve roots. We recently reported our acute comparative results of SNS vs PNS for various voiding dysfunctions, and the present study is a subset analysis of those with IC in that trial [9]. There have been no reports of chronic PNS in patients with IC, but a recent small study on overactive bladder was reported [10].…”
Section: Discussionmentioning
confidence: 88%
“…Spinelli and Peters and colleagues have used the tined lead used for InterStim therapy to chronically stimulate the pudendal nerve and have also reported promising results, with Peters reporting a possible superior effect of pudendal stimulation in a series of patients simultaneously implanted with both a sacral lead and pudendal leads. 62,63 Both series were small, however, and further study is needed.…”
Section: Figmentioning
confidence: 95%
“…In one study comparing pudendal nerve stimulation to sacral root stimulation, a majority of patients with non-neurogenic bladders preferred the pudendal nerve approach. 82 Flow receptors in the urethra are thought to mediate a micturition reflex, which can be triggered by stimulating the pudendal nerve trunk or branches to the urethra while the bladder is partially full. Studies in cats have established that specific stimulation patterns may be optimal for selection of the pudendal-mediated continence and micturition reflexes.…”
Section: Bladder Neuroprosthesesmentioning
confidence: 99%